The aarhus convention's third pillar in the EU from a procedural law perspective with special regard to regulatory acts - Gombos Katalin; Sziebig Orsolya Johanna (2020)
Since its adoption in 1998, the Aarhus Convention has become one of the most significant international environmental agreements. Its unique structure based on three pillars and the range of rights included in it also provides fundamental rights for individuals and organisations of the NGO sphere. However, accession to the Convention posed challenges for the European Union concerning the right of access to justice in environmental matters. The topic raises several procedural issues to which the Authors seek to approach with a thorough explanation that also considers the specificities of EU law. As a preliminary point, it can be said that the introduction of the category of regulatory acts and the development of case-law could only partially refine the CJEU's reluctance. The European Union is striving to be at the forefront of the political integration of environmental issues. Still, criticisms and dissenting views on the third pillar of the Aarhus Convention are increasingly calling into question the genuine commitment to the objectives of the international treaty. However, it is true, that due to the special legal order of the European Union, even the slightest changes can modify a whole range of procedural requirements concerning the CJEU's proceedings.